1993
DOI: 10.3758/bf03205199
|View full text |Cite
|
Sign up to set email alerts
|

Cortical involvement in visual scan in the monkey

Abstract: Monkeys performed a visual search task for food reward. Green square targets were embedded in 3 x 3 arrays of colored forms. In distinct-feature arrays, all nontarget stimuli were red diamonds, whereas in shared-feature arrays, some nontarget stimuli shared either form (red square) or color (green diamond) with the target. Reaction time was slower for shared-feature arrays and linearly related to the number of shared-feature distractors. Errors were more common in sharedfeature arrays, and shared-feature distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…Moreover there is a convergence of PET evidence indicating that BA45 is involved in transforming sublexical orthographic input into phonological output codes (Fiez, Balota, Raichle, & Peterson, 1999;Hagoort et al, 1999). It is also noteworthy that Bolster and Pribram (1993) postulated an analogous internal visual scanning processing involving parietal, frontal, and temporal cortices in explaining ERP feature-processing research with monkeys. As well, brain stimulation mapping of human subjects has implicated all three of these areas in phonemic identification (Ojemann & Mateer, 1979).…”
Section: Mewhort Model Of Word Recognitionmentioning
confidence: 99%
“…Moreover there is a convergence of PET evidence indicating that BA45 is involved in transforming sublexical orthographic input into phonological output codes (Fiez, Balota, Raichle, & Peterson, 1999;Hagoort et al, 1999). It is also noteworthy that Bolster and Pribram (1993) postulated an analogous internal visual scanning processing involving parietal, frontal, and temporal cortices in explaining ERP feature-processing research with monkeys. As well, brain stimulation mapping of human subjects has implicated all three of these areas in phonemic identification (Ojemann & Mateer, 1979).…”
Section: Mewhort Model Of Word Recognitionmentioning
confidence: 99%
“…The monkeys were required to foveate a target stimulus to receive a liquid reward but were granted a generous length of time so that they could freely visit whichever stimuli they wished to examine. Here we report on the behavioral performance of these animals as it relates to three specific issues that were not resolved in the previous visual conjunction search studies conducted with monkeys (Bichot and Schall 1999;Bolster and Pribram 1993;Buracas and Albright 1999;Motter and Belky 1998b).…”
Section: Introductionmentioning
confidence: 98%
“…We first asked whether the visual search strategies of monkeys are shaped by the composition of the stimuli within a search display. The original study of Bolster and Pribram (1993) showed that the latency of manual responses during conjunction search increases with the number of distractors sharing a feature with the target, suggesting only indirectly that visual strategies changed with display composition. Since then, the distractor-ratio effect has been examined in only one monkey and with search displays of varying number of stimuli (Buracas and Albright 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preliminary studies have measured reaction time as a function of set size (Dürsteler & von der Heydt, 1992;Buračas & Albright, 1997). A study by Bolster and Pribram (1993) in which monkeys reached toward the conjunction target revealed a very steep slope of 60 ms0item, and there were more errors to distractors that shared a target property than to distractors that shared none. However, the response latencies in this study were quite long and, unfortunately, saccades were not monitored.…”
Section: Introductionmentioning
confidence: 99%